A holistic literature review of building information modeling for prefabricated construction - Zhang, Shengxi; Li, Zhongfu; Li, Tianxin; Yuan, Mengqi (Journal of Civil Engineering and Management, 2021)
Building information modeling (BIM) and prefabricated construction (PC) are increasingly applied in the construction industry. Recent academic and industrial efforts indicated that the application of BIM and PC is a solution to reduce lifecycle costs, reduce waste, increase productivity and improve quality in construction. Although previous studies have advanced the integration of BIM and PC, extensive research scope and scattered research topics cannot form an overall picture of knowledge structure. Hence, this study aims to establish an up-to-date synthesis of the latest research on BIM for PC and identify the research gaps and future needs. First, a database with 103 journal articles on BIM for PC was established through data collection; second, a bibliometric analysis was applied to determine the top journals, articles and to map the latest mainstream research. Last, a qualitative analysis was used to determine the mainstream research areas and identify the research gaps and future needs. This study may contribute to enrich our body of knowledge on the use of the techniques in conjunction, help researchers and builders to understand the latest progress of BIM for PC research in timely fashion, and promote the integration of BIM with PC and other cutting-edge technologies moving forward.